Slope-based Empirical Path Loss Prediction Models for rural networks at 2.4 GHz - Fendji, Jean Louis Ebongue Kedieng; Mafai, Nelson Maguelva; Nlong, Jean Michel (Discoveries in Agriculture and Food Sciences, 2019)
Despite the plethora of works on empirical path loss prediction in wireless networks, just a little is addressing rural environments. In this work, we consider slope-based empirical path loss models in wireless networks at 2.4 GHz using off-the-shelf 802.11n (one transmitter and two receivers at 150Mbp and 300Mbps). We define three scenarios usually observed in rural environment. Subsequently, we do a measurement campaign and compare results to selected prediction models. We later propose a new model based on Liechty model. The new model is compared to Liechty model in Non-Line of Sight (NLOS) and combined (LOS and NLOS) scenarios. The Liechty model provided a better prediction in NLOS scenario while the new model outperforms in combined scenario. In addition, we observe that the data rate also influences the prediction. Especially in free space scenarios, the receiver with the greater data rate provides a smaller mean error and standard deviation.